Coupled Eulerian-Lagrangian simulation of spray-drying skimmed milk powder - Nualnuk, Pornpen; Sukpancharoen, Somboon; Srinophakun, Thongchai Rohitatisha (Agriculture and Natural Resources, 2024)
Importance of the work: Drying skim milk powder is a complex process dependent on the drying temperature, airflow and residence time distribution in the spray dryer. Stickiness can impact production. Objectives: To simulate the movement of particles within the spray dryer, and account for the observed stickiness of the skimmed milk powder. Materials & Methods: 1) The model was validated using available published data to determine model accuracy. 2) The model was used for airflow pattern prediction. 3) The particle residence time was predicted. 4) The stickiness was predicted in the context of the spray drying process. 5) The final component simulated the spray drying process itself. Results: A three-dimensional CFD simulation was performed for a co-current pilot plant spray dryer using a pressure nozzle for the purpose of spray drying skimmed milk powder. The simulated data agreed with published experimental findings, suggesting that the CFD simulations provided accurate predictions of the activity inside the spray dryer. The airflow comprised a core that flowed at high speed, with a slower zone of recirculation around the core. The particle trajectories depended upon the airflow patterns, resulting in the residence time of the smaller particles exceeding that of the larger particles. The deposits resulting from stickiness were typically on the walls of the conical section. Main finding: Stickiness arises during the process of spray drying, and this is important because it is a quality that can be utilized in controlling the potential enlargement of the particles. This can lead to better-quality powder.